The Effect Of Posyandu Education In The Elderly On Actions Of Utilizing Posyandu At Mawar Agung Posyandu Ceporan Village Gantiwarno Klaten - Suyamto (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Mawar Agung Elderly Posyandu there are 10 posts in Posyandu the number of elderly in Mawar Agung Elderly Posyandu, Ceporangantiwarno Klaten Village, is 531 elderly, 226 males, 305 females. Of the 531 who are active as many 140 and who are inactive as many as 391. Many of the elderly who are less active are due to lack of knowledge about Posyandu, so that health education is needed. The population in this study were 531 respondents and the sample was 90 with the division of 50 as the intervention group and 40 respondents in the control group. To determine the impact of health education on the use of posyandu for the elderly at the Mawar Agung Posyandu, Ceporan Village, gantiwarno, Klaten. The method that this reseach use is quasi-experimental design (quasi-experimental). The instrument used a questionnaire, data analysis was used with a paired sample t-test for a signifikan level 0.05.